Implementasi Checksum Dengan Menggunakan Algoritma Fletcher Untuk Mendeteksi Keaslian Sertifikat Rumah - Syifa, Syifa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
In today's era, renewal is continuously carried out in order to achieve better integrity. The issuance of certificates, which are usually printed on paper, is considered to be prone to damage and loss. Along with the times, certificates are now also issued in digital form. So many people switch to using certificates in digital form. So a mechanism is needed to help secure the certificate. Digital certificates can only be issued by authorized parties. Then the competent authority issues a certificate to another person who has the right to the certificate. Of course, the authenticity of the certificate information has been secured first through the checksum function so that the message in it is encrypted. In cryptography there are many methods and algorithms that can be used, one of which is the Fletcher checksum algorithm. The aim of Fletcher is to provide error detection properties that approximate cyclic redundancy checking but with lower computational effort associated with the summation technique. So that digital certificates that have changed will be detected as authentic.